2018
DOI: 10.1016/j.childyouth.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators for access to mental health services by traumatized youth

Abstract: Polytrauma is a highly prevalent public health problem in the U.S. with even higher rates in urban areas. Children with polytrauma often end up in multiple child-serving systems (e.g., mental health, child welfare, education, juvenile justice) with needs that are both complex and severe. Providers within these child-serving systems have potential to serve as gatekeepers to trauma services by linking youth with trauma-informed treatments and supports that promote recovery. The purpose of our study was to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…present five-years prior to the TBI event increased direct medical cost by up to 110%. Unfortunately, to date, care for individuals with TBI and mental health and/or addictions remains fragmented with lack of appropriate services and support for these individuals across the continuum of care [30][31][32]. This need for integrated healthcare has been recognized globally and across many health conditions and settings [33][34][35][36][37][38][39] and is particularly important for survivors of TBI because sequalae from TBI, including but not limited to increased impulsivity, slowed thinking, and impaired reasoning, problem solving and social communication [40,41], may lead to loss of stable housing, employment, and relationships [41,42].…”
Section: Plos Onementioning
confidence: 99%
“…present five-years prior to the TBI event increased direct medical cost by up to 110%. Unfortunately, to date, care for individuals with TBI and mental health and/or addictions remains fragmented with lack of appropriate services and support for these individuals across the continuum of care [30][31][32]. This need for integrated healthcare has been recognized globally and across many health conditions and settings [33][34][35][36][37][38][39] and is particularly important for survivors of TBI because sequalae from TBI, including but not limited to increased impulsivity, slowed thinking, and impaired reasoning, problem solving and social communication [40,41], may lead to loss of stable housing, employment, and relationships [41,42].…”
Section: Plos Onementioning
confidence: 99%
“…It is likely that present findings differ from previous research due to the method of data collection. Research in this area thus far has had a narrow scope and has mainly focused on the perspectives of providers (Chung et al, 2012; Damian et al, 2018; Paul, Gray, Elhai, Massad, & Stamm, 2006; Stewart et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This poster was graduating from university, and therefore would no longer have access to the university counselling service and the therapist they were seeing: The structural barriers identified in this study have previously been reported in the industry, where the impact of funding limitations, a complex and fragmented system, the high cost of care and lengthy wait times limit service accessibility for young people (Bendall et al, 2018;Bush, 2018). These barriers have also been highlighted by mental health service providers, adult service-users in primary healthcare and young people for trauma-related issues (Chung et al, 2012;Damian et al, 2018;Stewart et al, 2017). These included a lack of coordination and integration among services, workforce shortages, socioeconomic constraints and difficulties navigating the healthcare system.…”
Section: C Lack Of Power Over Therapy Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Practical barriers may also limit youth and families' access to community resources. For instance, it can be difficult for many families, particularly those living in rural or under-resourced areas, to access community resources that are located far from their homes, given challenges with reliable transportation and childcare (Damian, Gallo, & Mendelson, 2018).…”
mentioning
confidence: 99%